Skin Toxicity of Selected Hair Cosmetic Ingredients: A Review Focusing on Hairdressers - Symanzik, Cara; Weinert, Patricia; Babic, Zeljka; Hallmann, Sarah; Havmose, Martin Stibius; Johansen, Jeanne Duus; Kezic, Sanja; Macan, Marija; Macan, Jelena; Strahwald, Julia; Turk, Rajka; Van Der Molen, Henk F.; et al. (International Journal of Environmental Research and Public Health, 2022)
The safety assessment of cosmetics considers the exposure of a ‘common consumer’, not the occupational exposure of hairdressers. This review aims to compile and appraise evidence regarding the skin toxicity of cysteamine hydrochloride (cysteamine HCl; CAS no. 156-57-0), polyvi-nylpyrrolidone (PVP; CAS no. 9003-39-8), PVP copolymers (CAS no. 28211-18-9), sodium laureth sulfate (SLES; CAS no. 9004-82-4), cocamide diethanolamine (cocamide DEA; CAS no. 68603-42-9), and cocamidopropyl betaine (CAPB; CAS no. 61789-40-0). A total of 298 articles were identified, of which 70 were included. Meta-analysis revealed that hairdressers have a 1.7-fold increased risk of developing a contact allergy to CAPB compared to controls who are not hairdressers. Hairdressers might have a higher risk of acquiring quantum sensitization against cysteamine HCl compared to a consumer because of their job responsibilities. Regarding cocamide DEA, the irritant potential of this surfactant should not be overlooked. Original articles for PVP, PVP copolymers, and SLES are lacking. This systematic review indicates that the current standards do not effectively address the occupational risks associated with hairdressers’ usage of hair cosmetics. The considerable irritant and/or allergenic potential of substances used in hair cosmetics should prompt a reassessment of current risk assessment practices.
CRIS-Team Scopus Importer:2022-07-22
Keywords: cocamide diethanolamine; cocamidopropyl betaine; cosmet-ics; cysteamine hydrochloride; hairdresser; hairdressing; hand eczema; polyvinylpyrrolidone; polyvinylpyrrolidone copoly-mers; sodium laureth sulfate